Role-Play to Teach the Mental Status Exam - Linda Madson (Association of American Medical Colleges, 2011)
Abstract This resource is a 20- to 25-minute small-group role-play activity designed to teach vocabulary terms used in the psychiatric mental status examination. In this resource, learners are paired up, with one playing the psychiatric examiner and one playing the patient. Each team is given a psychiatric term and instructed to develop a 30- to 60-second clinical scenario illustrating the term. As each scenario is presented, classmates attempt to guess the term being portrayed. This exercise mimics the patient interview and allows students to experience mental status phenomena in a naturalistic setting. It also allows the instructor to dispel confusion regarding the meaning of closely related or unfamiliar terms used in the description of the mental status exam. This role-play has been used as a portion of the didactic presentation covering the mental status examination at the beginning of a psychiatry rotation for the last 5 years. Teaching evaluations have consistently listed the role-play as the most memorable portion of the didactic presentation. Sample comments include the following: "I really liked the role play. It helps reinforce definitions," "I think it is very helpful to see these terms in actions compared to just reading," "Fun and informative," "Helpful and will stick in my mind," "Going through vocabulary is helpful because they all seem similar at our level," and "The group work made it much easier to understand. That was a great idea."